Variables demográficas y reinfección por Malaria vivax en usuarios atendidos en el Hospital Regional de Loreto años 2022 al 2023 Iquitos 2025 - Lopez del Aguila, Dara Mishel (2025)
The objective was to determine the relationship between demographic variables and vivax malaria reinfection in users treated at the Loreto Regional Hospital from 2022 to 2023, Iquitos 2025. The method was quantitative, non experimental, descriptive, correlational and cross-sectional design. The population consisted of 140 medical records of users with a medical diagnosis of vivax malaria and the sample consisted of 103 medical records selected by random probability sampling. The technique used was documentary review and the instrument was the Demographic Data and Vivax Malaria Reinfection Registration Form. The processing was carried out in SPSS version 27.0 software, for univariate analysis, descriptive statistics were used and to analyze the relationships between variables, non-parametric inferential statistics, Chi Square (X²), was used, with a significance level α = 0.05. The results show that 45.6% of users were between 30 and 59 years old, 55.3% were male, 67.0% had a history of malaria, 56.3% had two or more previous episodes, 66.0% had fewer than 7 days of illness before starting treatment, and 37.9% were from Iquitos. Regarding vivax malaria reinfection, 50.5% did not experience reinfection, while 49.5% did. In conclusion, a significant statistical relationship was found with vivax malaria reinfection in the demographic variables: age (p= 0.021), sex (p= 0.022), history of malaria (p= 0.001), number of previous episodes (p= 0.001), time of illness before starting treatment (p= 0.021) and origin (p= 0.001).